Model Penyaluran Zakat Sebagai Instrumen Keuangan Sosial untuk mencapai Maqashid Syariah dengan menggunakan Pendekatan Analytic Network Process - Harianto, Syawal; Marliyah, Marliyah; Fuadi, Fuadi; Amin, Haris Al (Jurnal EMT KITA, 2021)
Islam requerer tompay zakat for wellbeing of Islamic people. Zakat is the forth of Islamic pillars. The contribution of zakat and maqashid syariah has the direct relations. This study aimed to know the relevale of zakat’s contribution to reach maqashid syariah with ANP method. ANP method is used to completed the problem in decomposition of synthesis and criterion scale. The study I s used techniques purposive sampling. Responden the study is expert and knowledgeable in this field (zakat). The result of this study showed the rank of each criterion from senif contribution of zakat. Senif fakir criterion is that have’nt anything. Senif miskin criterion is people that have the money less than the nisab. Senif amil criterion is mukallaf. Senif muallaf criterion is the new people in Islam religion. Senif gharimin criterion is the owed for his life. Senif fisabilillah criterion is established the dakwah center. Senif Ibnu sabil criterion is musafir for wealfare. The priority of maqashid syariah in senif contribution of zakat is religions. Then the priority contribution of zakat to reach maqasid syariah is fakir. The contribution of zakat should be distributed better for the welfare of muslims.